An efficient lightweight key exchange algorithm for internet of things applications - Fasila Kasfa Ali; Sheena Mathew (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Internet of things (IoT) gained wide popularity in recent years, and this is proved by tremendous increase in use of IoT applications worldwide. Distributed IoT applications can be implemented securely with the support of blockchain. By default, blockchain will ensure authentication of involved entities as well as integrity of data. Due to storage restrictions, use of hybrid system is preferred, and this involves cloud server for storage and blockchain for other functionalities. Data kept in cloud has to be encrypted by a strong encryption algorithm. Even though core security objectives are achieved, it is necessary to provide a secure method to exchange the key. Since, the key is the backbone of a security algorithm, protection of the key has to be ensured. In this work, an algorithm is proposed to provide a no-share key exchange between two communicating parties in a resource constrained environment. The same was implemented and compared with conventional key sharing algorithms. Security analysis was formally conducted by using widely accepted automated validation of internet security protocols and applications (AVISPA) tool and the proposed method proved to be secure.